2010
DOI: 10.1007/s11367-010-0156-7
|View full text |Cite
|
Sign up to set email alerts
|

EASEWASTE—life cycle modeling capabilities for waste management technologies

Abstract: Background, aim, and scope The management of municipal solid waste and the associated environmental impacts are subject of growing attention in industrialized countries. European Union has recently strongly emphasized the role of LCA in its waste and resource strategies. The development of sustainable solid waste management systems applying a life cycle perspective requires readily understandable tools for modeling the life cycle impacts of waste management systems. The aim of the paper is to demonstrate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The found 28 studies had 93 unique authors, from which only Christensen contributed more than one publication. He was one of the authors in publications [10] and [16]. Then by analyzing the found publications based on their publication channels, this study found three journals that included more than one article, contributing to the list of found 28 studies.…”
Section: Resultsmentioning
confidence: 99%
“…The found 28 studies had 93 unique authors, from which only Christensen contributed more than one publication. He was one of the authors in publications [10] and [16]. Then by analyzing the found publications based on their publication channels, this study found three journals that included more than one article, contributing to the list of found 28 studies.…”
Section: Resultsmentioning
confidence: 99%
“…the Technical University of Denmark has developed the EASEWASTE model (Environmental Assessment of Solid Waste System and Technologies) based on LCA, which quantifies the mass flow of substances and energy production and consumption (such as electricity and heat) in solid waste collection, transportation and different disposal processes (anaerobic digestion and composting, heat treatment, land use, resource sorting and recycling, landfill, etc. ), a spects such as energy consumption, greenhouse gas emissions and the environmental performance of disposal technologies (Bhander et al,2010). The SWM-GHG model (Solid Waste Management Green-House Gas) developed by the IFEU Institute in Germany was developed to compare different treatment schemes of municipal organic waste (including municipal organic waste), so the quantification of the environmental impact of different disposal technologies is relatively detailed, but the disposal technology included is rel atively limited (Bhander et al,2010).…”
Section: Introductionmentioning
confidence: 99%
“…), a spects such as energy consumption, greenhouse gas emissions and the environmental performance of disposal technologies (Bhander et al,2010). The SWM-GHG model (Solid Waste Management Green-House Gas) developed by the IFEU Institute in Germany was developed to compare different treatment schemes of municipal organic waste (including municipal organic waste), so the quantification of the environmental impact of different disposal technologies is relatively detailed, but the disposal technology included is rel atively limited (Bhander et al,2010). The CO2ZW model (CO2 Zero Waste) developed by the Autonomous University of Barcelona, Spain, is an Excel -based calculator that provides basic data sets for each stage of solid waste disposal in Mediterranean European c ountries, using specific waste data sets to estimate greenhouse gas emissions from municipal solid waste (Itoiz et al,2013).…”
Section: Introductionmentioning
confidence: 99%